MERITOCRACY IN SCHOOL QUALITY AND EDUCATIONAL QUALITY: ISLAMIC VOCATIONAL SCHOOLS IN BENGKULU CITY - Ali Akbarjono (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the implementation of a meritocratic system within school quality governance and its impact on enhancing educational quality in Islamic vocational schools in Bengkulu City. In this context, meritocracy emphasizes the management of quality assurance documentation, teacher competence, and student achievement based on actual ability (merit) rather than subjective factors or nepotism. The study employs a descriptive qualitative approach, utilizing case studies of several leading Islamic schools in Bengkulu City. Data were collected through interviews, observations, and document analysis. The findings indicate that Islamic schools consistently applying meritocratic principles—specifically in educator recruitment, performance assessment, and the standardization of religious facilities—successfully boosted graduate quality and the competitiveness of the madrasah. Key challenges include limited independent budgets and varying interpretations of quality assurance regulations. In conclusion, meritocracy serves as a crucial pillar for transforming Islamic education in Bengkulu City from a quantity-based model to one focused on quality.